Effectiveness of progressive dose-escalation of exenatide (exendin-4) in reducing dose-limiting side effects in subjects with type 2 diabetes - Fineman, Mark S.; Shen, Larry Z.; Taylor, Kristin; Kim, Dennis D.; Baron, Alain D. (Diabetes/metabolism research and reviews, 2004)
Background Exenatide (exendin‐4) exhibits dose‐dependent glucoregulatory activity, but causes dose‐limiting nausea and vomiting. This study was designed to formally assess the possibility of inducing tolerance to the side effects of nausea and vomiting at therapeutic doses of exenatide, using a dose‐escalation methodology. Methods In this two‐arm, triple‐blind, multicenter study, 123 subjects with type 2 diabetes were enrolled and randomized; 99 (80.5%) of them completed the study. Subjects in the exenatide‐primed arm received subcutaneous exenatide, starting at 0.02 µg/kg three times a day (TID) and increasing in 0.02 µg/kg per dose increments every 3 days for 35 days. Subjects in the exenatide‐naive arm received placebo TID for 35 days. At the end of this 35‐day regimen, subjects in both arms received the same highest dose of exenatide (0.24 µg/kg TID) for 3 days. Thus, the exenatide‐naive arm received exenatide for the first time on Day 35. Results The exenatide‐primed arm had a lower proportion of subjects experiencing nausea and vomiting in response to exposure to the highest dose of exenatide (27 vs 56% in the exenatide‐naive arm; p = 0.0018). Kaplan–Meier estimates of cumulative incidence were 0.28 in the exenatide‐primed arm, compared with 0.68 in the exenatide‐naive arm (p ≤ 0.001). As predicted by the study design, fewer subjects in the exenatide‐primed arm reported severe nausea (29%) and vomiting (10%) than those in the exenatide‐naive arm (48 and 31%, respectively). In the exenatide‐primed arm, fasting serum glucose progressively declined over the first 35 days of dosing, but was unchanged in the exenatide‐naive arm (placebo phase) during the same interval. Conclusion Gradual dose‐escalation of exenatide successfully reduced the proportion of subjects experiencing dose‐limiting nausea and vomiting, with no loss of glucoregulatory activity, thus demonstrating the value of gradual dose‐escalation in mitigating the gastrointestinal side effects of exenatide. Copyright © 2004 John Wiley & Sons, Ltd.